Spatiotemporal Changes of Near-Surface Ozone Concentration From 2015 to 2018 in Beijing - Xie, Junfei; Shi, Shengwei; Wu, Lingyun; Zhang, Xin (Frontiers in Environmental Science, 2021)
In this study, we investigated the spatiotemporal changes of near-surface O3 concentration based on 33 automatic air quality monitoring stations in Beijing in 2015 and 2018. Here we show that the diurnal variations for O3 concentration at 33 monitoring stations exhibited a single-peak mode with a minimum concentration from 06:00 to 07:00 and a maximum value from 14:00 to 15:00. We find that the O3 concentration was significantly positively correlated with the air temperature, solar total radiation, and wind speed, while it was negatively correlated with the relative humidity. Among those factors, the air temperature played the most important role in influencing O3 concentration (relative contribution is greater than 88% in the boosted regression trees model). We also present that the annual variation of O3 concentration at all stations tended to be a “bell-shaped” curve distribution with a peak in summer and the lowest value in winter. The annual averaged O3 concentration at 33 stations in Beijing was 57.5 ± 9.8 μg⋅m−3 in 2015 and 60.3 ± 9.0 μg⋅m−3 in 2018. In addition, we detect that the annual averaged value of the O3 concentration was lower in the central and southern Beijing, and higher in the northern Beijing both in 2015 and 2018. The spatial difference of the O3 concentration could be explained by the traffic pollution, vegetation coverage, atmospheric regional transmission, and atmospheric particulate matter concentration.